(untitled) (Journal of Applied Learning and Teaching, 2020)
The growth of blended and online learning within the higher education sector has required academic staff to develop new skills and confidence in delivering online pedagogy that successfully engages students. Previous research indicated it would be beneficial for staff to develop a common understanding of best practice in learning and teaching using asynchronous discussion boards. The aim of this research was to investigate use of the online Guide by facilitators, who are responsible for developing and facilitating online discussion boards and supporting students’ digital engagement. Findings of previous research was used to inform development of the Guide. Additionally, a review of peer-reviewed and grey literature was undertaken. The researchers collaborated during a series of production workshops to plan, develop and write the Guide. Two members of the team assisted with conversion of the product into an open access online tool hosted by the University of Tasmania learning and teaching website. Feedback regarding the structure and content was embedded on the website to enable users to suggest improvements. Google Analytics data was collected monthly and ePrint data was also monitored. Findings over a 12-month period indicated the Guide was predominantly accessed by Australian users, although there has been growth in downloads of chapters from other English speaking countries. Reports indicate a high proportion of new sessions each month, peaking with the need to ‘super speed’ learning and teaching online due to COVID-19 health and well-being restrictions within the higher education sector, indicating that the Guide is appealing to a growing global audience.